Can a white Canadian write a post-colonial text ? - Miguel Nenevé (Ilha do Desterro)
Gareth Griffits and Helen Tiffin), post-colonial literature is the literature produced by those people formerly colonized by British and other European empires. The authors state that the term post-colonial covers “all the cultures affected by the imperial process from the moment of colonization to the present day.”2 Furthermore, post-colonial literatures are those literatures written by people affected by colonialism or by “cultures which suffered the experience of colonization” and had to fight against imperial dependence. Thus, they believe that it is possible to study Canadian literature within a post-colonial context.